IMPLEMENTASI CANVA PADA PEMBELAJARAN MENULIS KOMIK STRIP (TEKS ANEKDOT) KELAS X AKT 1 SMK NEGERI 1 POGALAN - Widyatama, Wahyu; Sujinah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of Canva as a learning medium in developing comic strip writing skills within the Indonesian language subject. Using a descriptive qualitative approach, data were collected from students of class X AKT 1 through observation techniques. Data analysis was conducted descriptively to provide a comprehensive overview of the research object. The findings indicate that 36 students in class X AKT 1 successfully utilized Canva to create comic strip projects creatively and innovatively according to their respective themes. It can be concluded that Canva is an effective medium for Indonesian language learning, particularly for anecdote text materials in comic strip format.